Can JWH‐210 and JWH‐122 be detected in adipose tissue four weeks after single oral drug administration to rats?. (29th January 2014) - Schaefer, Nadine; Peters, Benjamin; Bregel, Dietmar; Maurer, Hans H.; Schmidt, Peter H.; Ewald, Andreas H.
ABSTRACT Synthetic cannabinoids such as alkylindole derivatives entered the illicit drug market worldwide a few years ago. Only a few data are available concerning their pharmacokinetics, in particular their distribution and persistence in adipose tissue. For the present study, rats were administered a single 20 mg/kg oral dose of JWH‐210 or JWH‐122. After one month, they were dissected and adipose tissue was taken in order to study whether JWH‐210 and JWH‐122 persisted in this body sample. After extraction, the samples were analyzed by liquid chromatographic–mass spectrometry (LC‐QTrap‐MS). Validation of the analytical method for adipose tissue is also presented. The results of the matrix effects determination ranged between 30.6 and 43.8%. The limits of detection for JWH‐210 and JWH‐122 were 0.8 and 1.0 ng/g and lower limits of quantification were 3.7 and 2.1 ng/g, respectively. Calibration curves ranged from 10 to 75 ng/g for JWH‐210 and from 5 to 50 ng/g for JWH‐122. Intra‐ and interday precision values were lower than 15% and bias values within ±15%. Applying this method, in adipose tissue specimens obtained 4 weeks after single drug administration, JWH‐210 and JWH‐122 were detected in concentrations of 116 and 9 ng/g, respectively. Copyright © 2014 John Wiley & Sons, Ltd.